2022
DOI: 10.47144/phj.v55i1.2158
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Patients and Their Presentation in Acute Coronary Syndrome With Outcomes: Does Gender Play Role?

Abstract: Objectives: To determine the frequency of different acute coronary syndrome (ACS) presentations and their outcomes in diabetic patients and gender based difference. Methodology: This cross sectional study was conducted in Cardiology Department of Khyber Teaching Hospital, Peshawar from 1st January to 31st July 2018. Diabetic patients admitted via emergency department presenting with acute coronary syndrome were included .The patients were followed during their hospital stay for complications like left ventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Our results concur with the aforementioned Pakistani study. 9 It similarly revealed that the risk of mortality is 2.58% in diabetic males and 1.58% in females, which is again in correspondence with our analysis regarding the mortality rate of CAD in diabetic patients based on gender. Our single-centrebased study was conducted on most patients who were uneducated about their condition and unaware of maintaining a proper medical history of their cardiovascular disease.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results concur with the aforementioned Pakistani study. 9 It similarly revealed that the risk of mortality is 2.58% in diabetic males and 1.58% in females, which is again in correspondence with our analysis regarding the mortality rate of CAD in diabetic patients based on gender. Our single-centrebased study was conducted on most patients who were uneducated about their condition and unaware of maintaining a proper medical history of their cardiovascular disease.…”
Section: Discussionsupporting
confidence: 90%
“…Another institute in Pakistan reported an almost similar pattern in their ndings. 9 Regarding the outcomes of CAD, there was a significant gender-wise dierence. Congestive heart failure was observed in 43.9% of males and 22.4% of females, re-angina was observed more in the female patients as compared to the male patients (19.3% vs 40.8%) and mortality was higher in the male patients as compared to female patients (15.8% vs 4.1%).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Increased incidence of adverse outcomes among diabetic patients after PCI is well reported by various other studies as well. 9,[17][18][19] Further multi-center large-scale studies are required in our population to highlight the clinical importance and impact of diabetes mellitus on the clinical course and prognosis of STEMI patients. Even though this study was performed at the largest cardiac care center of the country, single-center coverage and a limited number of study subjects remained the main limitation of this study.…”
Section: Discussionmentioning
confidence: 99%